Direct measurement of new particle formation based on tethered airship around the top of the planetary boundary layer in eastern China. (15th July 2019) - Qi, Ximeng; Ding, Aijun; Nie, Wei; Chi, Xuguang; Huang, Xin; Xu, Zheng; Wang, Tianyi; Wang, Zilin; Wang, Jiaping; Sun, Peng; Zhang, Qiang; Huo, Juntao; et al.
Abstract: New particle formation (NPF) is one main source of atmospheric aerosols and plays an important role in global climate by contributing up to two thirds of the atmospheric cloud condensation nuclei. Numerous studies on characteristics and mechanisms of near-surface NPF have been conducted in last decades. However, the characteristics of NPF around the top of the planetary boundary layer (PBL) remains unclear due to the limitations of vertical measurements. In this study, a tethered airship onboard with advanced particle instruments was deployed for directly measurement of the NPF exactly above and under the top of the PBL in the Yangtze River Delta (YRD) of eastern China in December 2017. Coupled with the real time ground Lidar observation, we successfully conducted measurement of aerosol size distribution, chemical components of aerosol and gas pollutants with 100 m above/under the top of the PBL. Despite not being observed within the PBL during the flight and at three ground sites in YRD, NPF event with the growth rate of 3.8 nm/h was detected above the PBL. High oxidizing capacity, enough condensable vapors and low condensation sink above the PBL favor the onset of NPF. Model simulation and the aerosol chemical composition result indicate the important role of gaseous sulfuric acid in NPF and its subsequent growth in the upper atmosphere. Our study highlights the potential mechanism of NPF above the PBL and the need of direct vertical measurements to better understand NPF in the atmosphere and its climate effect. Highlights: Tethered airship platform made it possible to understand subtle vertical structure. Model forecast and online measurements can reduce the risk of experiment. New particle formation was detected only above the planetary boundary layer. The growth rate above the planetary boundary layer was about 3.8 nm/h. High H2 SO4 values above planetary boundary layer favor the new particle formation.